(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
This article discusses the beneficial effects of simple physical therapy methods on human health. Special attention is paid to methods such as jars, mustard plasters, oxygen therapy, compresses, ice compresses, hydropathy and massage. The analysis of their therapeutic effect on human organism has been carried out, as well as mechanisms of their action and scope of application in medical practice. It has been found that these methods contribute to improving blood circulation and reducing inflammation.